Penyelesaian Sengketa Ekonomi Syari'ah Sebagai Sebuah Kewenangan Baru Peradilan Agama - Rifyal kabah (Jurnal Hukum IUS QUIA IUSTUM, 2006)
UnderAct No. 3 ontheYear 2006, Islamic Court has additional authority such as syari'ah  economy. Formerly, the dispute settlement between Syari'ah Bank and its customers's  based on agreement and contract between them, whether mudharobah ormurahabah.  Before the existence ofthe Specific Syari'ah Economic Act, there isagreat possibility for  the judges to handle the Syari'ah Economy case based on contract law, whether Fiqh or  Civil Code.